THE ROLE OF SPEAKING PRACTICES ON GRAMMAR LEARNING - Setyowati, Luluk (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
AbstractGrammar is one of determining points of mastering English. It refers to a set of the structural rules of language which concerns with the grammar in any given natural language. Communicative competence would have revealed that it gives no endorsement for the neglect of grammar. Students of Plantation processing technology program of Politeknik kelapa Sawit Citra Widya Edukasi face difficultiy in learning grammar because of the perceptions that grammar is trict and boring. However, English lecturer finds a way to cope with the problem by using communicative grammar approach. Implement speaking practices can motivate students in learning grammar. The difficulty that is usually faced by students related to learning grammar is memorizing the many grammar rules. Remembering grammar alone does not help students to master grammar easily. That is because of the method of memorizing makes students easy to forget so it will be easier to remember grammar while practices speaking. The findings show that speaking on grammar learning, students become more motivated and confident to learn grammar. Communicative learning grammar can change the perceptions of students who have assumed that grammar is difficult to become learning that is easy and fun. In addition, student confidence also increased.Keyword: Speaking, Communicative Grammar, Learning MotivationÂ